Les accrus de frêne dans les Pyrénées Centrales : un avenir énergétique local ? - Bernard Elyakime; Laurent Larrieu; Alain Cabanettes; Laurent Burnel (Revue de Géographie Alpine)
While the agricultural economy of Central Pyrenean is steadily declining, natural forest stands progress on agricultural mountainous meadows. For these forest extensions, we define the economic conditions of a new fuel-wood local economy. But it is possible that the forest owner makes himself logging, hauling and carriage to meet his heating needs, for a highest benefit from 11.2 to 22.3 €/st. So, an economy based on wood energy, with woods coming from private natural extension forests, is possible. It is based on an appropriate regional policy that will stimulate the necessary initiatives of forest owners of spontaneous ash reforestations to harvest these forest extensions.